NEGOTIATION BETWEEN TRADITIONAL LEADERS AND RELIGIOUS LEADERS IN MANAGING CUSTOMARY CONTROVERSIES CONTRADICTING ISLAMIC LAW IN AEK NABARA BARUMUN: Negosiasi Tokoh Adat dan Tokoh Agama dalam Pengelolaan Kontroversi Adat yang Bertentangan dengan Syariat di Aek Nabara Barumun - Fahrur Rozy Pulungan; Suheri Harahap (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study examines the negotiation process between traditional leaders and religious leaders in addressing the controversy surrounding same-clan marriages in Aek Nabara Barumun, which are perceived as conflicting with Islamic law. The issue arises because the local community continues to uphold customary regulations prohibiting marriages between individuals of the same clan as a form of respect for cultural values and ancestral heritage, while Islamic teachings permit such marriages as long as no mahram (prohibited kinship) relationship exists. These differing perspectives have generated social dynamics that require resolution through communication and deliberation to prevent conflict within the community. This study aims to understand how the negotiation process is carried out by traditional and religious leaders and to examine the role of negotiation in maintaining a balance between customary values and Islamic principles. A qualitative approach with a phenomenological design was employed. Data were collected through in-depth interviews, observations, and documentation involving traditional leaders, religious leaders, community members, and other supporting informants in Aek Nabara Barumun. The findings reveal that deliberation and persuasive approaches constitute the primary mechanisms for resolving the controversy over same-clan marriages. Traditional leaders seek to preserve customary practices as an essential component of the community’s cultural identity, whereas religious leaders emphasize the importance of conformity with Islamic law. The study also finds that the community is more receptive to social compromise than to direct prohibition, as customary traditions continue to hold strong cultural significance. Therefore, negotiation serves as a crucial mechanism for maintaining social harmony and balancing customary traditions with religious values within the community.